TINJAUAN FIKIH MUAMALAH TERHADAP PRAKTIK LIVE SELLING DENGAN SISTEM FLASH SALE: MITIGASI UNSUR GHARAR DALAM DESKRIPSI PRODUK - Nor Khaliza; Naila Mawaddati; mulyanti, rusnia; sauqi, muhamad (Jurnal Syariah dan Ekonomi Islam, 2026)
The development of digital technology has created new ways of conducting economic transactions, such as direct selling, flash sales, and online shopping through e-commerce sites. This convenience can make buying and selling more active, but it can also create uncertainty in transactions. This study aims to analyze direct selling using a flash sales system according to Islamic law. The method used is to examine various studies on muamalah jurisprudence, direct selling, flash sales, and online transactions. The results indicate that the practice is permissible as long as it adheres to the principles of honesty, openness, clarity of the transaction object, and agreement between the seller and buyer. However, uncertainty can arise if product information or transaction rules are not clearly explained. Therefore, it is important to provide complete and honest product descriptions to ensure transactions comply with Islamic law.